Multi-energy Microgrids Incorporating EV Integration : Optimal Design and Resilient Operation - Masrur, Hasan; Shafie-khah, Miadreza; Hossain, M. J.; Senjyu, Tomonobu (IEEE, 2022)
There are numerous opportunities and challenges in integrating multiple energy sources, for example, electrical, heat, and electrified transportation. The operation of multi-energy sources needs to be coordinated and optimized to achieve maximum benefits and reliability. To address the electrical, thermal, and transportation electrification energy demands in a sustainable and environmentally friendly multi-energy microgrid, this paper presents a mixed integer linear optimization model that determines an optimized blend of energy sources (battery, combined heat and power units, thermal energy storage, gas boiler, and photovoltaic generators), size, and associated dispatch. The proposed energy management system seeks to minimize total annual expenses while simultaneously boosting system resilience during extended grid outages, based on an hourly electrical and thermal load profile. This approach has been tested in a hospital equipped with an EV charging station in Okinawa, Japan through several case studies. Following a M1/M2/c queuing model, the proposed grid-tied microgrid successfully integrates EVs into the system and assures continued and economic power supply even during grid failures in different weather conditions.
Keywords: batteries; Cogeneration; Electric vehicle charging; EV; Grid outages; Multi-energy Microgrids; optimization; Resilience; Resistance heating; Simulation and optimization; microgrids; fi=Sähkötekniikka|en=Electrical Engineering|